Activity of immobilized papain dehydrated by n-propanol in low-water media - Theppakorn T. (2014)
A propanol-rinsed enzyme preparations (PREP) of papain showed an activity of 59 nmol min-1 (mg powder)-1 in tert-butanol at the optimal water activity of 0.2. The immobilized papain was stable in aqueous media for 3 d at 4°C. Solid-state buffers (bases and their HCl salts) suspended in the organic medium decreased the initial rate in all cases tested. The operational stability during Z-Gly-Phe-NH2 synthesis was improved when solid cysteine was added, doubling the yield after 24 h.